2022
DOI: 10.1128/spectrum.01874-22
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Immunoglobulin Response to Nontuberculous Mycobacteria Infection in People with Cystic Fibrosis

Abstract: Lung infections with nontuberculous mycobacteria (NTM), and particularly Mycobacterium abscessus , a pathogen with high antibiotic resistance, are of great concern due to poor clinical outcomes and challenging detection in people with cystic fibrosis and other diseases. Standard detection methods are insensitive and increasingly difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…The role of IgG in limiting disease within the lungs may be complemented by surfactant proteins A and D, which can opsonize mycobacteria ( 62 ). Our data differ from studies showing that NTM infections result in high levels of circulating IgG and IgA, which can be used to diagnose NTM infection ( 63 , 64 ). This difference could be due to the longer chronicity of disease in humans.…”
Section: Discussioncontrasting
confidence: 99%
“…The role of IgG in limiting disease within the lungs may be complemented by surfactant proteins A and D, which can opsonize mycobacteria ( 62 ). Our data differ from studies showing that NTM infections result in high levels of circulating IgG and IgA, which can be used to diagnose NTM infection ( 63 , 64 ). This difference could be due to the longer chronicity of disease in humans.…”
Section: Discussioncontrasting
confidence: 99%
“…Our studies focused on the role of non-immune plasma. We have previously demonstrated that anti-Mab IgG exist in NTM-infected people with CF (41), but the role of specific immunity on opsonization and killing will require further study. Finally, these studies focus on neutrophils; the role of complement for other immune cells working and in vivo effects require further study.…”
Section: Discussionmentioning
confidence: 97%
“…The role of IgG may be limited within the lungs since surfactant proteins (SP) A and D may opsonize mycobacteria [74]. Other studies showed that NTM infections result in high levels of circulating IgG and IgA which can be used to diagnose NTM infection [75, 76]. Moreover, it has been shown that antibodies have a functional role in the control of TB [77].…”
Section: Discussionmentioning
confidence: 99%